2015
DOI: 10.12809/hkmj144259
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging features of vascular leiomyoma of the ankle

Abstract: Vascular leiomyoma is a benign soft tissue tumour with a predilection for middle-aged women. It is most often seen in the extremities, particularly in the lower leg. The typical lesion is a small, slow-growing subcutaneous nodule. These tumours are often unexpected or preoperatively confused with other soft tissue tumours including low-grade sarcomas, leading to wide surgical excision. This may partly be due to the relatively few studies delineating the characteristic imaging features of this entity. Here, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The presence of pain may be helpful in narrowing the diagnosis of angioleiomyoma but is unreliable as only 58% of tumors present with pain . Preoperative imaging studies such as ultrasound or angiography can show the vascularity of the lesion but also cannot accurately diagnose angioleiomyoma . Angioleiomyoma is most often treated with surgical excision, considered a safe and effective method of treatment with few cases of tumor reoccurrence …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pain may be helpful in narrowing the diagnosis of angioleiomyoma but is unreliable as only 58% of tumors present with pain . Preoperative imaging studies such as ultrasound or angiography can show the vascularity of the lesion but also cannot accurately diagnose angioleiomyoma . Angioleiomyoma is most often treated with surgical excision, considered a safe and effective method of treatment with few cases of tumor reoccurrence …”
Section: Discussionmentioning
confidence: 99%
“…2 Preoperative imaging studies such as ultrasound or angiography can show the vascularity of the lesion but also cannot accurately diagnose angioleiomyoma. 16 Angioleiomyoma is most often treated with surgical excision, considered a safe and effective method of treatment with few cases of tumor reoccurrence. 1,3 Histopathologically, angioleiomyoma appears as an encapsulated proliferation of eosinophilic smooth muscle cells with minimal nuclear pleomorphism.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Yoo [ 18 ], involving eight patients, demonstrates an iso-signal in T1, hyper-signal in T2, and enhancement after gadolinium injection, more or less homogeneously. The study by Alta [ 10 ], describing 26 lesions on MRI, corroborates these radiological characteristics. Our results are consistent with the existing literature.…”
Section: Discussionmentioning
confidence: 53%
“…Clinically, angioleiomyomas typically present as solitary, well-defined, gradually enlarging masses. They frequently elicit pain or tenderness upon palpation and predominantly emerge in the skin and subcutaneous tissues, notably in the upper [ 2 , 3 , 4 , 5 , 6 , 7 ] and lower limbs [ 8 , 9 , 10 ]. However, occurrences in other anatomical sites, including the trunk, head, and neck [ 11 , 12 ], and even intra-abdominally [ 13 ], have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Angioleiomyoma is difficult to be diagnosed before surgery and it should be considered a possible diagnosis when a well-demarcated mass of isointense signal to muscle on T1WI, heterogeneous high signal intensity on T2WI, heterogeneous strong enhancement, and an adjacent tortuous vascular structure is seen in the extremities [ 15 ]. Alta YT Lai et al retrospected and analyzed the MRI features of 37 cases of vascular leiomyomas, the results showed that on T1WI, most of the cases showed isointense or slightly high signal intensity compared to adjacent muscle, a few cases showed heterogeneous or low signal intensity; and on T2WI, all the cases indicated high signal intensity; their review results also demonstrated that on gadolinium enhanced T1WI, about 42% were homogeneous enhancement, 39% were heterogeneous enhancement and only one case showed peripheral enhancement [ 16 ]. The case 1 in the current report had the similar MRI characteristics as above which showed isointense compared to adjacent muscle on TIWI and peripheral enhancement on gadolinium enhanced T1WI.…”
Section: Discussionmentioning
confidence: 99%